Pengelolaan dan Pengembangan Sistem Informasi Manajemen di Kantor Polisi - Pagan, Syahrial Alas Putra (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of the research is to learn about the management and development of management information systems in the police offices. This method is aimed at gaining a deep understanding of the problem rather than making generalizations. Observations, interviews, literature, and questionnaires are some of the methods of gathering data. The conclusion that the author can take after completing the Document Management Information System and Public Service at the City Resort Police Office Tebing High is as follows, facilitating the City resort Police Office in the preparation of reports, public services and facilitates in the search for documents. The proposed system uses a database that helps to organize the data of complaints reports and public services so that the data are integrated together as well as facilitated in the process of search, retrieval of the necessary data. With this application will be able to generate a percentage of crime in the area of the Resort Police Office of Tebing High City according to the number of criminal cases